2015
DOI: 10.1016/j.jbiomech.2014.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Corner height influences center of mass kinematics and path trajectory during turning

Abstract: Despite the prevalence of directional changes during every-day gait, relatively little is known about turning compared to straight gait. While the center of mass (COM) movement during straight gait is well characterized, the COM trajectory, and the factors that influence it, are less established for turning. This study investigated the influence of a corner’s height on the COM trajectory as participants walked around the corner. Ten participants (25.3 ± 3.74 years) performed both 90° step and spin turns to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…10). Only a few researchers have used the COM-COP angle in turning or circular walking tasks [32, 33]. The peak ML COM-COP angle is around 7.0° for healthy subjects, while the ML angle (FCP) in our study for CW1 m with NSL is around 6.9° (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…10). Only a few researchers have used the COM-COP angle in turning or circular walking tasks [32, 33]. The peak ML COM-COP angle is around 7.0° for healthy subjects, while the ML angle (FCP) in our study for CW1 m with NSL is around 6.9° (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…A slip occurs at the shoe and floor interface when the friction required (required coefficient of friction, RCOF) to support walking exceeds the friction available (available coefficient of friction, ACOF) at the shoe and floor interface (Hanson, Redfern, and Mazumdar 1999). The RCOF for straight walking has been investigated extensively (Hanson, Redfern, and Mazumdar 1999; Cham and Redfern 2002a; Kim, Lockhart, and Yoon 2005; Chang, Matz, and Chang 2012; Anderson, Franck, and Madigan 2014; Beringer, Nussbaum, and Madigan 2014; Fino and Lockhart 2014; Fino, Lockhart, and Fino 2015). The transverse component of the ground reaction force obtained with a force plate has been ignored in most of the RCOF calculations, but a study conducted by Chang, Chang, and Matz (2011) demonstrated that the transverse shear force could significantly increase RCOF and result in a much earlier occurrence of RCOF in the gait cycle.…”
Section: Biomechanicsmentioning
confidence: 99%
“…The transverse component of the ground reaction force obtained with a force plate has been ignored in most of the RCOF calculations, but a study conducted by Chang, Chang, and Matz (2011) demonstrated that the transverse shear force could significantly increase RCOF and result in a much earlier occurrence of RCOF in the gait cycle. Recent studies showed that the RCOF for turning could be as high as 0.36, while that for straight walking was of the order of 0.2 (Burnfield, Tsai, and Powers 2005; Yamaguchi et al 2013; Fino, Lockhart, and Fino 2015). The RCOF for carrying out different tasks under different situations, such as walking on different floor surfaces with different footwear, needs to be investigated further.…”
Section: Biomechanicsmentioning
confidence: 99%
“…Additionally, Yamada et al [ 13 ] reported a greater frequency of spin turns during a multi-target stepping task in elderly with a high risk of falling compared to healthy elderly. The higher frequencies of spin turns are concerning because the COM is laterally displaced outside the BOS more during spin turns than step turns [ 9 , 10 ] indicating a high risk of lateral falls if a perturbation (slip, trip) occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Spin turns are characterized by turning on the ipsilateral limb (e.g., left turn while the left limb is the stance limb) and step turns are characterized by turning on the contralateral limb (e.g., left turn while the right limb is the stance limb). Of these two strategies, spin turns are considered less stable than step turns because the whole-body center-of-mass (COM) remains outside the base-of-support (BOS) for the majority of the stance phase [ 9 , 10 ]. Because of this COM displacement, one could expect step turns to be more prevalent.…”
Section: Introductionmentioning
confidence: 99%